A formação da subjetividade na Idade Mídia (The formation of subjectivity in the Media Age) - Zuin, Antônio Álvaro Soares; Gomes, Luiz Roberto (Revista Eletrônica de Educação, 2019)
In today’s society of the spectacle, the screens are present in all spheres of public and private spaces, in such a way that it becomes possible to characterize the current society as the Media Age. This omnipresence of screens in all social relations determines unprecedented transformations in both the objective and the subjective dimensions. It is no coincidence that it is possible to identify signs of addictive behaviour in relation to audio-visual stimuli continuously produced and consumed through electronic gadgets, with emphasis on the ubiquitous presence of mobile devices. Following this line of reasoning, it becomes increasingly common to intensify anxiety, if someone separates from their cell phone for example. Given this context, the main objective of this article is to reflect critically on the metamorphoses in the subjective dimension present in the so-called Media Age. In order to do so, we will present considerations about the transformations related to the concept of cultural industry in the era of the microelectronic revolution, as well as the analysis of the changes in subjectivity resulting from the reconfiguration of the public and private spheres in times of hegemony of digital technologies. Resumo Na atual sociedade do espetáculo, as telas estão presentes em todas as esferas dos espaços público e privado, de tal maneira que se torna possível caracterizar a sociedade hodierna como a da Idade Mídia. Esta onipresença das telas em todas as relações sociais determina transformações inéditas tanto na dimensão objetiva, quanto na subjetiva. Não por acaso, já é possível identifcar sinais de comportamento de vício em relação aos estímulos audiovisuais continuamente produzidos e consumidos por meio dos gadgets eletrônicos, com destaque para a presença ubíqua dos aparelhos celulares. Seguindo esta linha de raciocínio torna-se cada vez mais comum o recrudescimento da ansiedade, caso alguém se separe de seu celular, por exemplo. Diante de tal contexto, os autores deste artigo têm, como principal objetivo, refletir criticamente sobre as metamorfoses na dimensão subjetiva presentes na chamada Idade Mídia. Para tanto, serão apresentadas considerações sobre as transformações no conceito de indústria cultural na era da revolução microeletrônica, bem como a análise das modifcações na subjetividade decorrentes da reconfiguração das esferas pública e privada em tempos de hegemonia das tecnologias digitais. Keywords: Subjectivity, Media Age, Cultural Industry, Microelectronic Revolution. Palavras-chave: Subjetividade, Idade Mídia, Indústria Cultural, Revolução Microeletrônica. References ADORNO, Theodor W. Educação e emancipação. Trad. Wolfgang Leo Maar. Rio de Janeiro: Paz e Terra, 1995. ADORNO, Theodor W. “A indústria cultural”. In: COHN, Gabriel (Org.), Theodor W. Adorno, coleção grandes cientistas sociais, São Paulo: editora Ática, 1994a. ADORNO, Theodor W. “Sobre música popular”. In: COHN, Gabriel (Org.), Theodor W. Adorno, coleção grandes cientistas sociais, São Paulo: editora Ática, 1994b. ADORNO, Theodor W. Minima Moralia: reflexões a partir da vida danificada. Trad. Luiz Eduardo Bicca. São Paulo: Ática, 1993. ADORNO, Theodor W.; HORKHEIMER, Max. Dialética do esclarecimento: fragmentos filosóficos. Tradução de Guido Antonio de Almeida. Rio de Janeiro: Jorge Zahar editor, 1986. ARENDT, Hannah. A condição humana. Trad. Roberto Raposo. Rio de Janeiro: Forense Universitária, 2017. CABOT, Mateu; LASTÓRIA, Luiz A. C. N.; ZUIN, Antônio, A. S. (Coords.). Tecnologia, violência, memória: diagnósticos críticos de la cultura contemporánea. Barcelona: Anthropos; México: Universidad Autónoma Metropolitana - Iztapalana, 2018. 270p. DARDOT, Pierre; LAVAL, Christian. Comum: ensaio sobre a revolução no século XXI. Trad. Mariana Echalar. São Paulo: Boitempo, 2017. HABERMAS, Jürgen. Entre naturalismo y religião. Madrid: Technos, 2005. HABERMAS, Jürgen. Direito e democracia: entre facticidade e validade. Rio de Janeiro: Tempo Brasileiro, 2003. 2 v. 2003a – volume 1 e 2003b – volume 2. HABERMAS, Jürgen. Mudança estrutural da esfera pública: investigações quanto a uma categoria da sociedade burguesa. Trad. Flávio R. Kothe. Rio de Janeiro: Tempo Brasileiro, 1984. HABERMAS, Jürgen. Theorie des kommunikativen Handelns - Band 1 und 2. Frankfurt am Main: Suhrkamp Verlag, 1981. HABERMAS, Jürgen. Técnica e ciência como ideologia. Trad. Artur Morão. Lisboa: Edições 70, 1968. HABERMAS, Jürgen. Strukturwandel der Öffentlichkeit. Neuwied und Berlin: Hermann Luchterhand Verlag, 1962. HEW, Khe F. Students’ and teachers’ use of Facebook, Computers in Human Behaviour, 27, 662-676, 2011. HORKHEIMER, Max. Teoria tradicional e teoria crítica. Coleção os Pensadores. São Paulo: Editora Abril, 1987. HORKHEIMER, Max; ADORNO, Theodor W. Dialética do esclarecimento. Rio de Janeiro. Jorge Zahar, 1985. KANT, Immanuel. Resposta à pergunta: que é esclarecimento? In: Textos seletos. Petrópolis: Vozes, 1985. LUHMANN, Niklas. Soziale Systeme: Grundriss einer allgemeinen Theorie. Frankfurt am Main: Suhrkamp, 1994. MARTINS, Sandra Olades. A esfera pública: dos salões à rede virtual. In: BORGES, Bento Itamar; GOMES, Luiz Roberto; JESUS, Osvaldo Freitas de (Orgs.) Direito e democracia em Habermas: pressupostos e temas em debate. São Paulo: Xamã, 2010. MAZER, Joseph P.; MURPHY, Richard E.; SIMONDS, Cheri J. I will see you on “Facebook”: The effects of computer-mediated teacher self-disclosure on student motivation, affective learning, and classroom climate, Communication Education, 56 (1), 1-17, 2007. McLUHAN, Marshall. Os meios de comunicação como extensão do homem. São Paulo: Cultrix, 1969. NOBRE, Marcos. A teoria crítica. Rio de Janeiro: Jorge Zahar Editor, 2004. TÜRCKE, Christoph. Erregte Gesellshaft: Philosophie der Sensation, München: C.H. Beck Verlag, 2002. TÜRCKE, Christoph. Sociedade excitada: filosofia da sensação. Tradução de Antônio Zuin, Fabio Durão, Francisco Fontanella e Mario Frungillo. Campinas: Editora da Unicamp, 2010.